Pemanfaatan Lahan Perkarangan Sebagai Sumber Penghasilan Tambahan bagi Ibu-ibu Rumah Tangga di Jl. Merawan 14 RT.31 RW.07 Kelurahan Sawah Lebar Kecamatan Ratu Agung Kota Bengkulu - Neri Susanti; Kamelia Astuty; Nirta Vera Yustanti; Ahmad Soleh; Yun Fitriano (Universitas Dehasen Bengkulu, 2023)
Utilization of land Yard is open land that is around the house. During the pandemic, most people are tired of staying at home. To overcome this boredom, one of which can be done by utilizing the yard of the house. Utilization of yard land will provide benefits for family life such as: a source of food and also as a source of income. One of the agricultural technologies that can be applied to utilize the yard is hydroponic technology. Hydroponics is a technique of cultivating plants without using soil as a planting medium. The advantage of plants cultivated by the hydroponic method is that the results of Forgetfulness are higher with better yield quality. The prospects for developing a hydroponic business are very good, especially in urban areas, because land in urban areas is very narrow as a result of land conversions such as for housing, offices, shops and roads. Narrow land is suitable for agricultural businesses using hydroponic technology. The awareness of city people is getting higher to maintain their health by consuming good quality vegetables and fruits. Several types of vegetable plants that can be cultivated with a hydroponic system include: lettuce, celery, cauliflower, pakchoy, takecay and so on. This is very profitable for the community, especially housewives on Jl. Merawan 14 in order to be able to utilize the yard as a source of additional income and for daily needs.